2014
DOI: 10.1007/s00404-014-3605-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum endocan concentration in women with pre-eclampsia

Abstract: These findings suggest that the role of endocan in the pathogenesis of pre-eclampsia was not related to pre-eclampsia; hence, further studies are needed to investigate the role of endocan in the pathogenesis of pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…Studies have shown an increase in CEC number and other markers of EC damage such as soluble vascular cell adhesion molecule-1 (sVCAM-1), E-selectin and endocan in PE compared with Norm-Preg women (Canbakan et al, 2007; Adekola et al, 2015; Tuzcu et al, 2015; Cakmak et al, 2016), although some studies reported no difference in serum endocan levels (Yuksel et al, 2015). Other studies have shown a decrease in circulating endothelial progenitor cells as a marker of endothelial damage in PE women (Sakashita et al, 2014) (Table 1).…”
Section: Endothelial Dysfunction In Preeclampsiamentioning
confidence: 99%
“…Studies have shown an increase in CEC number and other markers of EC damage such as soluble vascular cell adhesion molecule-1 (sVCAM-1), E-selectin and endocan in PE compared with Norm-Preg women (Canbakan et al, 2007; Adekola et al, 2015; Tuzcu et al, 2015; Cakmak et al, 2016), although some studies reported no difference in serum endocan levels (Yuksel et al, 2015). Other studies have shown a decrease in circulating endothelial progenitor cells as a marker of endothelial damage in PE women (Sakashita et al, 2014) (Table 1).…”
Section: Endothelial Dysfunction In Preeclampsiamentioning
confidence: 99%
“…It has been suggested to be a new biomarker for endothelial dysfunction and PE (751, 752). It would appear, however, to be a rather less specific inflammatory biomarker (753, 754) and is associated with a variety of diseases, including chronic kidney disease (755, 756) and cardiovascular disease (755). Most pertinently from our perspective, it is also raised strongly during sepsis (757760).…”
Section: Proteomic and Similar Biomarkers – Circulating And Placentalmentioning
confidence: 99%
“…These results suggest that endocan may be a functional protein rather than a simple biomarker. Interestingly, it has also been suggested that change of circulating endocan may be a marker of women with preeclampsia [18][19][20][21][22][23][24][25]. However, results of previous pilot studies are inconsistent [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has also been suggested that change of circulating endocan may be a marker of women with preeclampsia [18][19][20][21][22][23][24][25]. However, results of previous pilot studies are inconsistent [18][19][20][21][22][23][24][25]. Some studies showed that circulating endocan may be higher in women with preeclampsia than those with normal pregnancy [18,20,22,24], while others did not find a significant difference regarding the circulating endocan between pregnant women with and without preeclampsia [19,21,23,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation